(untitled) (Journal of Pharma Insights and Research, 2024)
Kawasaki disease (KD) is a rare, self-limiting vasculitis predominantly affecting children under the age of five. We report a case of a 5-year-old boy presenting with fever, generalized maculopapular rash, peeling of lips, erythematous oral mucosa, lymphadenopathy, and nail changes. The patient was admitted to the pediatric ward with a 3-day history of low-grade fever, rash, and vomiting episodes. Physical examination revealed bilateral lymphadenopathy in the cervical, axillary, and inguinal regions. Laboratory investigations showed elevated white blood cell count, neutrophilia, platelet count, alkaline phosphatase, aspartate aminotransferase, C-reactive protein, and erythrocyte sedimentation rate. The antistreptolysin O titer was positive, indicating recent streptococcal infection. Based on the clinical presentation and diagnostic criteria, a diagnosis of Kawasaki disease was established. The patient was treated with intravenous ceftriaxone, azithromycin, pantoprazole, and supportive therapy, including paracetamol, antihistamines, zinc, and topical calamine lotion. After 15 days of treatment, the patient showed improvement and was discharged with a planned follow-up. This case highlights the importance of early recognition and prompt treatment of Kawasaki disease to prevent potential complications, such as coronary artery aneurysms. Increased awareness among pediatricians is crucial for timely diagnosis and management of this rare vasculitis syndrome, especially in developing countries where cases may go undetected